A systematic video analysis of 69 injury cases in World Cup alpine skiing - Bere, T.; Flørenes, T. W.; Krosshaug, T.; Haugen, P.; Svandal, I.; Nordsletten, L.; Bahr, R. (Scandinavian Journal of Medicine & Science in Sports, 2014)
We have limited insight into how injuries occur in professional ski racing. The aim of this study was to describe the injury situations in World Cup alpine skiing. Injuries reported through the International Ski Federation Injury Surveillance System for three consecutive World Cup seasons (2006-2009) were obtained on video. In total, 69 injuries and 124 runs of matched controls were analysed by five experts to evaluate the skiing situation, skier behavior, as well as piste-related factors. A chi-square test (95% CI, P </= 0.05) was used to examine whether there was a difference between course sections regarding where the injury situation occurred. The skier was most frequently turning (n = 55) or landing from a jump (n = 13) at the time of injury. Most of the injuries to the head and upper body (96%) resulted from crashes, while the majority of knee injuries (83%) occurred while the skier was still skiing. Gate contact contributed to 30% of the injuries, while 9% occurred at contact with safety nets/material. Almost half of the injuries (46%) occurred in the final fourth of the course. A particular concern was the high contribution of inappropriate gate contact and the high-energy impacts to the body when crashing.